Nonlinear wave effects of curvature solitons in surface layers of high-purity aluminum polycrystals under severe plastic deformation. II. The role of boundary conditions, interfaces, and nonequilibrium of a deformed state; Physical Mesomechanics; Vol. 11, iss. 5-6, Sept.-Dec. - Panin V. E. Viktor Evgenyevich; Elsukova T. F.; Vaulina O. Yu.; Pochivalov Yu. I. (2008, 2008)
Mechanisms of alternating severe plastic deformation at mesoscale levels of high-purity thin aluminum foils were investigated. Polycrystalline foils of varying thickness were glued to more rigid commercial titanium or aluminum substrates and the resulting two-layer specimens were then subjected to alternating bending. This provided a marked difference in boundary conditions between the front and back sides of the foils and enabled a crucial role of the combined effect of normal tensile and compressive stresses on the development of plastic deformation of the test materials to be demonstrated. The examined mechanisms of localized plastic deformation and its self-organization at mesoscale levels are controlled by the field of maximum tangential stresses and resulting rotational deformation modes. Free foil surfaces undergoing severe plastic deformation exhibit porosity strongly dependent on the foil thickness. No porosity is observed on back sides of all examined foils. Very thin slip and tweed structures seen in thin foils are attributed to "chessboard-like" distribution of tensile and compressive stresses over internal interfaces. The influence of the extent of nonequilibrium of the state of materials subjected to severe plastic deformation on the mechanisms of deformation involved is interpreted in terms of the nonequilibrium thermodynamics of local structural phase transformations in zones of hydrostatic tension